Sustainability: Mechanized Handling of Large-Scale Livestock's Cow Manure Factors Into a Greener Economy - Roong Ratikul; Somchai Seviset; Songwut Egwutvongsa (My University, 2023)
This research objective is to develop a large-scale livestock cow manure processing machine to add economic value and be environmentally friendly. The population was 4,994 dairy farmers in Nakhonratchasima province, Thailand. The sample group was the dairy farmers group in Pak Chong district Nakhonratchasima province, Thailand, with a total of 357 people. By evaluating the rating scale (Rating Scale) five levels of Likert. and there was a confidence value with an alpha coefficient (Cronbach's Alpha = 0.703), which was analyzed by SLR systematic literature review and scamper analysis by synthesizing the data to design new products as three main issues were 1) product creation guidelines from SLR literature review 2) problem diagnosis to the solution with SCAMPER technique 3) new product design in accordance with GOAL data were analyzed by multiple regression analysis and confirmatory factor analysis which found that 1) factors machine features 2) the efficiency factor of the machine and 3) image factors of the machine that resulted positively on farmer satisfaction and explained the farmer satisfaction variance of 71.9%. The standard score regression equation was Z= .453(X_1 )+ .384(X_2 )+ .465(X_3 ) and the regression equation in raw score y ?=-1.20+.460(X_1 )+.385(X_2 )+.466(X_3 ). When evaluated with CFA, the satisfaction of the sample group of dairy farmers group with the developed cow dung separate machine was found. That is the result of 3 factors according to the model concordance index: ?^2= .874, df = 4, relative ?^2= .219, p-value = .928, RMSEA = .000, RMR = .004, GFI = .996, AGFI = .956, NFI = .998, TLI = 1.078, PGFI = .089, RFI = .980, AIC = 82.874

Received: 18 August 2023 / Accepted: 25 October 2023 / Published: 5 November 2023
Keywords: Agricultural Systems and Practices